Morphological variability in different isolates of Chaetomium globosum - and DV SINGH, S. KHAYUM AHAMMED, RASHMI AGGARWAL* (Indian Phytopathology, 2005)
Chaetomium globosum, an ascomycetous fungus, belonging to the order Sordariales, family Chaetomiaceae has been identified as a potential antagonist of Bipolaris sorokiniana. The fungus produces numerous hairy perithecia in culture. The morphology of perithecia and ascospores has been studied by means of optical and scanning electron microscope. The perithecia were 180 x 153 to 316.8 x 284.8 11m, in isolates Cg2 and Cg4 respectively. The ascospores size of all the isolates were almost similar, smallest size being shown by isolate Cg9 (9.6 X 8.4 11m). Perithecia showed densely haired surfaces and the shape of perithecia varied from globose to subglobose. The ascospores released inside the perithecium were seen oozing out from osteole like cirrhus. Under SEM, the shape of perithecia could not be ascertained, as they were densely covered with stiff hairs having depositions. Ascospores under SEM were lemon shaped, smooth surfaced with apical papillae.